2018
DOI: 10.1103/physrevb.98.235114
|View full text |Cite
|
Sign up to set email alerts
|

Infinite boundary conditions for response functions and limit cycles within the infinite-system density matrix renormalization group approach demonstrated for bilinear-biquadratic spin-1 chains

Abstract: Response functions Ax(t)By(0) for one-dimensional strongly correlated quantum many-body systems can be computed with matrix product state (MPS) techniques. Especially, when one is interested in spectral functions or dynamic structure factors of translation-invariant systems, the response for some range |x − y| < is needed. We demonstrate how the number of required time-evolution runs can be reduced substantially: (a) If finite-system simulations are employed, the number of time-evolution runs can be reduced fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…(iii) For the ULS point, S (q, ω) is gapless at q = ±2π/3 and exhibits three thresholds in the spinon continuum as shown in Fig. 6 (d), which is in excellent agreement with the Bethe ansatz solution 39,66 .…”
Section: B Numerical Results and Analysessupporting
confidence: 66%
“…(iii) For the ULS point, S (q, ω) is gapless at q = ±2π/3 and exhibits three thresholds in the spinon continuum as shown in Fig. 6 (d), which is in excellent agreement with the Bethe ansatz solution 39,66 .…”
Section: B Numerical Results and Analysessupporting
confidence: 66%
“…We have explored the low-energy physics of isotropic spin-1 chains. Using an MPS algorithm [26], we were able to compute precise dynamic structure factors, even in the highly entangled critical phase with c = 2. We have found that the NLσM and the Majorana field theory fail to capture the influence of the biquadratic term and provide only a rather unsatisfactory description for the Haldane phase.…”
Section: Discussionmentioning
confidence: 99%
“…While the groundstate phase diagram has been studied extensively, much less is known about the low-energy dynamics. We use a recently introduced algorithm [26] based on the density matrix renormalization group (DMRG) [27][28][29] and the time evolution of matrix product states (MPS) [30][31][32] with infinite boundary conditions [33,34] to compute dynamic structure factors S(k, ω) = x e −ikx dt e iωt ψ| Âx (t) B0 (0)|ψ ,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They originated from the understanding that the density matrix renormalization group (DMRG) technique could be recast in a variational formulation by means of matrix product states (MPS) [6][7][8]. This stimulated the further development of such a framework in the last decade, extending the TN paradigm to encompass higher dimensionality [9][10][11][12][13][14], peculiar geometries [15,16], directly addressing the thermodynamical limit [17][18][19], as well as the continuum [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%